Analysis of Sea Surface Temperature with Total Suspended Solid Algorithm Based on Satellite Images Data - Wibisana Hendrata; Sukotjo B. M; Lamento Umbro (Nusantara Science and Technology Proceedings)
Sea surface temperature and total suspended solid known as a parameter that is widely used by researchers to detect the quality of water whether it is waters that exist in a river, lakes or on the coast. The changes from the climate will affect the sea surface temperature of water, and whether in total suspended solid the changes can significantly affect the value of sea surface temperatures on the coast. The method developed for analyzing is done by compiling a mathematical model algorithm from the satellite image reflectance data to obtain a model of the SST value and TSS concentration for the same time periods and then analyzing the SST correlation to TSS, and the results shown that TSS which obtained from the most suitable algorithm is linear with the formula TSS = 5799,4x + 13,449 with the correlation value is 0,9275 and for the mapping of sea surface temperature, the most suitable algorithm is linear at a wavelength of 443 nm with the formula SST = -445, 06x + 33,654 and the value of the correlation is 0.6103, and this research could be concluded that the correlation between total suspended solids and sea surface temperature aren’t significant because of the result only have the correlation value 0,329 with the standard error 1,602.